2010
DOI: 10.1007/s00542-010-1076-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic actuation and sensing micro-device for mechanical response of cultured adhesive cells

Abstract: As one of the cellular responses to external mechanical stimulation, it is presumable that the cell adjusts the cytoskeletal mechanical strength globally as well as locally. However, the methodologies to validate this hypothesis are extremely limited and expensive. In this study, a new micro device, utilizing dynamic response of a piezoelectric vibrator, is developed, which works not only to evaluate local mechanical property, but also to enforce local mechanical stimulation onto cultured living adhesive cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The microforce sensors on micropost arrays have therefore served as actuators and sensors simultaneously on one chip. The integrative approach for active force probing was to include functional sensing and actuation elements onto the chip [114]. Advances in microfabrication techniques permit the application of mechanical stretching to single cells or a small population of cells with enhanced control of forces and displacements [115,116].…”
Section: Integration Of Controlled Function For Load Applying and Man...mentioning
confidence: 99%
“…The microforce sensors on micropost arrays have therefore served as actuators and sensors simultaneously on one chip. The integrative approach for active force probing was to include functional sensing and actuation elements onto the chip [114]. Advances in microfabrication techniques permit the application of mechanical stretching to single cells or a small population of cells with enhanced control of forces and displacements [115,116].…”
Section: Integration Of Controlled Function For Load Applying and Man...mentioning
confidence: 99%
“…Several studies have reported that well-controlled dynamic stimulations are able to promote abilities of cell proliferation, growth and recovery from damage [12][13][14][15][16][17]. Likewise, the appropriate mechanical stimulations may have the potential to raise the efficiency and speed of the differentiation of the iPS cells into the objective cells.…”
Section: Introductionmentioning
confidence: 99%
“…A review article by Fujita in 1994 highlighted the importance of applying micro machines to manipulate microorganisms or biomolecules. 1 There have been numerous designs proposed for bio-grippers, whose actuating mechanism includes thermal, 2,3 static electric, 4 piezoelectric, 5 direct mechanical contact approaches, 6,7 and so on. However, thermal and static electric actuation methods might damage the bio-specimen with its thermal and electrical power; using piezoelectric material the converting efficiency needs to be taken into consideration; and using the direct mechanical contact method it is hard to accurately control over micro-scale movement.…”
Section: Introductionmentioning
confidence: 99%